Stereotype Construction in Disney's Retellings of Grimms' Fairy Tales: An Intertextual and Discursive Inquiry - Rusnalasari, Zulidyana D.; Retnaningdyah, Pratiwi; Mustofa, Ali (Acitya Wisesa: Journal of Multidisciplinary Research, 2023)
through Disney's animated adaptations of three canonical Grimm fairy tales, namely Snow White and the Seven Dwarfs (1937), Cinderella (1950), and Sleeping Beauty (1959). Employing intertextual analysis, critical discourse analysis, and reader-response inquiry, the study pursues a twofold aim: to identify the narrative and discursive strategies through which Disney transforms its Grimm source texts, and to investigate how these adapted representations are received and retained by non-Western audiences. Textual analysis reveals that Disney's hypertextual adaptations systematically excise moral complexity, punitive justice, and female agency from the Grimm originals, replacing them with romantic resolution, passive femininity, and Eurocentric beauty ideals that equate physical appearance with moral worth. Semi-structured interviews with 164 undergraduate students at an Islamic university in Indonesia demonstrate that Disney's versions have effectively displaced the Grimm originals from participants' cultural memory, with nearly all respondents referencing the Disney adaptations as their sole point of narrative familiarity. Participants consistently described Disney through affective rather than critical frameworks, reflecting the studio's capacity to embed normative gender and moral ideologies within emotional and mnemonic structures that persist into adulthood. These findings extend prior Western-centered reception studies into a non-Western context and contribute to ongoing scholarly discourse on media imperialism, critical media literacy, and the pedagogical implications of globalised children's entertainment.